Hamming Code in JPEG Image Steganography within the Discrete Cosine Transform Domain - Zulfikar, Dian; Hermanto, Hermanto (Journal of Applied Informatics and Computing, 2025)
This study proposes a novel JPEG image steganography method that combines Least Significant Bit (LSB) embedding in the Discrete Cosine Transform (DCT) domain with Hamming Code (2k − 1, 2k − k − 1) to minimize the number of modified DCT coefficients. Experiments were conducted on images with varying resolutions (512×512, 1024×1024, 2048×2048) and JPEG quality factor of 75, where PSNR (Peak Signal to Noise Ratio) and SSIM (Structural Similarity Index) parameters are used to measure the quality and similarity between the original image and the stego image. The method achieved an embedding capacity of up to 524,288 bits, with an average PSNR of 39–41 dB and SSIM above 0.98. Compared to conventional techniques such as JSteg and F5, the proposed approach demonstrates improved embedding capacity, better visual quality, and higher resistance to statistical steganalysis, making it suitable for secure and efficient data hiding applications.